Activation of selected trunk muscles during symmetric functional activities in poststroke hemiparetic and hemiplegic patients. Issue 2 (1st February 1999) - Dickstein, Ruth; Heffes, Yael; Laufer, Yocheved; Ben-Haim, Zvika
Abstract : OBJECTIVE: To compare the EMG activity between the recti abdominii muscles and between the lumbar erector spinae muscles in hemiparetic and hemiplegic patients during functional symmetric trunk movements and to compare patients' EMG activity profiles with those of healthy controls.. METHODS: EMG activity from the selected muscles was recorded during three symmetric and time controlled trunk exercises. Data analysis was based on values of cross correlations and of ratios between EMG activity of the bilateral corresponding muscles. RESULTS: In all groups, the highest cross correlations were obtained for both muscles when the muscles acted as prime movers. For the recti abdominii muscles, these values in the patients were comparable with those of the healthy subjects, whereas for the extensor muscles, the highest synchronous activity was displayed in healthy subjects and the lowest in hemiplegic patients. Laterality differences in the amount of EMG activity of the recti abdominii muscles were not biased towards one side. For the extensor muscles, in the controls, the activation levels were higher in the left erector spinae muscle than in the right one in two of the three exercises. Similarly, in the extensor muscles of the hemiparetic patients, activity on the paretic side was higher than on the non-paretic side in two exercises. CONCLUSIONS: In patients with a supratentorial poststroke hemiparesis or hemiplegia, bilateral corresponding axial trunk muscles co-contract during symmetric trunk activities. Synchronous activation is at its highest level during voluntary dynamic tasks and is greater in the recti abdominii than in the erector spinae muscles. For both muscles, EMG activation levels on the paretic side were not lower than on the non-paretic side. Thus, the assertion that the muscles on the paretic side are activated to a lesser extent than their counterparts on the non-paretic side during symmetric trunk movements was not confirmed.